How similar is similar? Exploring the binary and ternary solid solution landscapes of p-methyl/chloro/bromo-benzyl alcohols. Issue 4 (5th January 2017) - Romasanta, A. K. S.; Braga, D.; Duarte, M. T.; Grepioni, F.
Abstract : Binary and ternary solid solutions formed by p -chlorobenzyl alcohol, p -bromobenzyl alcohol and p -methylbenzyl alcohol have been prepared by co-melting and melting point variation of the solid solutions investigated. Abstract : New binary and ternary solid solutions formed by p -chlorobenzyl alcohol ( p -ClBA), p -bromobenzyl alcohol ( p -BrBA) and their quasi-isostructural compound p -methylbenzyl alcohol ( p -MeBA) have been prepared and characterized by DSC and powder X-ray diffraction. The binary and ternary solid solutions were synthesized by co-melting of p -MeBA/ p -ClBA, p -MeBA/ p -BrBA and p -ClBA/ p -BrBA and by co-melting of p -MeBA/ p -ClBA/ p -BrBA in various molar ratios. By varying the relative concentrations, it has been possible to observe the consequent variations of the melting points of the solid solutions. For the binary 1 : 1 p -MeBA/ p -BrBA and p -ClBA/ p -BrBA compounds, single crystals were grown from solution and their structures were investigated by X-ray diffraction.